Endangered species : a reference handbook - Randall, Jan A. (Contemporary world issues., 2018)
This book begins with an introduction that addresses major threats and extinctions in history, discusses the geographical and cultural contexts in which these incidents happened, highlights other key moments along the endangered species timeline, and clearly shows why the topic of endangered species matters.